MENDAYAGUNAKAN TEKNOLOGI DAN KEARIFAN LOKAL SEBAGAI SUMBER KREASI DAN INOVASI KERJA - Sarumaha, Martiman S. (Universitas Nias Raya, 2022)
The purpose of this service is to provide socialization to the campus community on how to utilize technology and take advantage of local wisdom values. The method of implementing this service in the form of lectures conveys to participants to be able to utilize technology in developing the potential for local wisdom that has high selling value. This service activity was carried out at the South Nias Education Foundation Campus. The results of this dedication are expected to fix this country, especially the Nias archipelago, it needs cold hands and an iron hand and a clean heart to turn Nias island into a leading area in western Indonesia, so it requires investment in superior human resources through education as the key to progress, maintaining local culture as local wisdom to be a source of learning.